CHARACTERIZATION OF UPDRAFT TYPE COAL GASIFICATION WITH EQUIVALENCERATIO VARIATIONS: KARAKTERISASI GASIFIKASI BATUBARA TIPE UPDRAFT DENGAN VARIASI EQUIVALENCERATIO - Ryanda Putra Nasution (LPPM UPMI, 2023)
The research was carried out using experimental methods to determine the gas resulting from the coal-based gasification process. Research was conducted at UD. Gending Sidoarjo on a dual fuel PLTD demo plant. The reactor is made of refractory stone which is insulated with a layer of cement and covered with iron which is rolled into a tube shape to maintain the temperature and so that the heat losses that occur are not too large. The reactor has overall dimensions with a height of 3.7 m and an internal diameter of 1.8 m. Control of the temperature that occurs at each stage of the gasification process is carried out by installing 3 thermocouples. The first thermocouple (T1) is located at 100 cm from the bottom of the reactor, the second thermocouple (T2) is located at 150 cm from the bottom of the reactor, and the third thermocouple (T3) is located at the top cover of the gasifier and has a length of 2 meters. The 4th thermocouple (T4) is located on the burner, whose function is to determine the temperature when the syngas burns in the burner. Based on the research results, it shows the visualization of the color of the flame resulting from burning syngas at an ER of 0.36. The picture above shows that the color of the fire is predominantly yellow from the base to the tip. Meanwhile, there is only a little orange color in the base area. This shows that the flame temperature is starting to decrease compared to when burning syngas with an ER of 0.31. This is reinforced by figure 4.4 which shows that the flame temperature when burning syngas with an ER of 0.36 is 672 oC and has an HHV of 3749.50 kJ/m3. shows a visualization of the color of the syngas combustion flame at ER 0.4. From the picture above, you can see that the color of the fire is predominantly yellow from the base to the tip. This shows that the fire has a low temperature. This is reinforced by data from Figure 4.4 which shows that the syngas burning fire has a temperature of 667 oC and has an HHV of 2579.85 kJ/m3 so it has a lower temperature than syngas burning with an ER of 0.36. From the picture above you can also see the influence of the large syngas discharge causing the fire to approach horizontal. The temperature in the burner has a lower temperature than the temperature in the partial oxidation zone, this is due to the simple design of the burner and the energy lost by radiation. If the burner design and thermocouple placement are improved by taking into account nozzle geometry, turbulence and other factors, the temperature at the burner can be higher than the temperature in the partial oxidation zone.